Are College-Educated Police Officers Different? A Study of Stops, Searches, and Arrests - Johnson, Thaddeus (2018)
A study of more than 60,000 police traffic stops found that college-educated officers were more likely than other officers to stop drivers for less serious violations, perform consent searches, and make arrests on discretionary grounds. These results are consistent with those of prior research indicating that college-educated officers are more achievement oriented and eager for advancement based on the traditional performance criteria of stops, searches, and arrests. The results raise questions regarding the recommendation of the President’s Task Force on 21st Century Policing (2015) to improve police-community relations by hiring more college-educated police officers, especially in urban communities where concerns about over policing are widespread. If community engagement were to become a primary basis for professional advancement, however, the current results suggest that college-educated officers may adapt to the new standards as diligently as they have to the traditional criteria for reward and promotion in U.S. police departments